Black tonal level reproduction in pulse‐width‐modulated high dynamic range displays. Issue 2 (2nd November 2020) - Boitard, Ronan; Ploumis, Stelios; Kumaran, Raveen; Damberg, Gerwin; Ballestad, Anders
Abstract: High dynamic range (HDR) workflows provide increased peak luminance and lower black levels leading to a significantly enhanced quality of experience. HDR pixels also represent more tonal values across the dynamic range by using a higher bit‐depth along with different perceptual transfer functions. However, many light‐emitting display devices modulate light using a limited bit‐depth in the linear domain. It is thus challenging for such display systems to achieve simultaneously high peak luminance and high amount of information in the shadows. In this paper, we summarize pulse‐width modulation (PWM) principles and its impact on low black level reproduction. We then assess the required bit‐depth to accurately reproduce shadow information of an HDR signal for different display capabilities. Finally, we describe several technology improvements that could improve the tonal level reproduction of PWM‐driven displays. Abstract : High dynamic range (HDR) workflows provide increased peak luminance and lower black levels leading to a significantly enhanced quality of experience. HDR pixels also represent more tonal values across the dynamic range by using a higher bit‐depth along with different perceptual transfer functions. However, many light‐emitting display devices modulate light using a limited bit‐depth in the linear domain. It is thus challenging for such display systems to achieve simultaneously high peak luminance and high amount of information in the shadows. In this paper, we summarize pulse‐width modulation (PWM) principles and its impact on low black level reproduction. We then assess the required bit‐depth to accurately reproduce shadow information of an HDR signal for different display capabilities. Finally, we describe several technology improvements that could improve the tonal level reproduction of PWM‐driven displays.